PEMANFAATAN BARANG BEKAS PADA PEMBUATAN MEDIA PEMBELAJARAN KIKAPOL (KINCIR, KARTU, DAN POHON LITERASI) UNTUK KEGIATAN LITERASI SANGGAR ANAK SUNGAI DELI: Penelitian Deskriptif - Fransiska Naibaho; Judia Immanuel Siregar; Louis Agustina Br Keliat; Natasyah Br Sitepu; Prontina Situmorang; Riwanto Supriadi Sinaga; Sumitri Romaito Pane; Nurdalilah; Nurhafni Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to increase children's interest and motivation in reading and creativity in making KIKAPOL learning media (Kincir, Kartu, and Pohon Literasi) that utilize used goods in literacy activities at the Sanggar Anak Sungai Deli. Literacy activities in this studio aim to improve children's reading and writing skills through interesting, creative, and environmentally friendly media. By utilizing used goods, this study evaluates solutions to increase the effectiveness of literacy learning while reducing waste. The results of the study indicate that the use of KIKAPOL media based on used goods can significantly increase children's interest in reading and literacy skills